(untitled) (World Economics and Finance Bulletin, 2025)
Sustainable development emerged as a response to adverse environmental impacts and the failure of traditional models to achieve a balance among economic growth, social justice, and environmental protection. This study examined the historical evolution of the sustainable development concept by reviewing its various stages and highlighting the global agreements and conferences that have contributed to shaping this concept and formulating comprehensive sustainability policies. Moreover, the research reviewed several sustainable development models, including the Triple Circles Model, the Capital Stock Model, the Prism Model, the Sustainability Egg Model, and the Atkisson’s Pyramid Model, demonstrating that these frameworks endeavor to balance economic, social, environmental, and cultural dimensions. Additionally, the study discussed criticisms directed at some of these models, notably the ThreeLegged Chair Model, which has been critiqued for failing to sufficiently acknowledge the role of humans within the ecosystem. Ultimately, the research concluded that sustainable development represents an inclusive framework aimed at achieving balance across various developmental dimensions, while emphasizing the necessity of equitable resource redistribution and ensuring the sustainability of resource use for future generations.